Pengolahan Air Embung Alam Tampungan Hujan Morowudi dengan Kombinasi Pretreatment Geotekstil dan Teknologi Filtrasi - Yohanita Anggraini, Viona; Pungut, Pungut; Widyastuti, Sri; Nur Rohim, Imam; Ratnawati, Rhenny (Jurnal Sains & Teknologi Lingkungan, 2025)
There has been an exceedance of water quality standards in the Morowudi Village reservoir. Therefore, treatment using a combination of geotextile pretreatment and filtration is required. The objective of this study is to determine the reduction in turbidity, color, and total coliform concentrations in the Morowudi reservoir water and to identify the most optimal efficiency of each variation in reducing turbidity, color, and total coliform concentrations. The turbidity, color, and total coliform concentrations of Morowudi reservoir water were 84.9 NTU, 251 TCU, and 730,000 CFU/100 mL, respectively. This laboratory-scale study used geotextile pretreatment as the initial filter, followed by filtration. The geotextile pretreatment reactor is a cylindrical tube with dimensions of 40 cm x 50 cm. Treatment is conducted in stages from the geotextile pretreatment reactor to filtration. The filtration reactor has a length of 10 cm, width of 10 cm, and height of 90 cm. In the filtration reactor, variations in the height of silica sand, zeolite, and activated carbon media are tested. In variation 1, the heights of the silica sand, zeolite, and activated carbon media were 30 cm, 20 cm, and 20 cm, respectively. In variation 2, the heights of the silica sand, zeolite, and activated carbon media were 20 cm, 30 cm, and 20 cm, respectively. Based on the research results, in variation 1, the average reduction in turbidity concentration was 19.39 NTU with a reduction percentage of 77.16%, color concentration was 85.40 TCU with a percentage of 65.98%, and total coliform was 2.60%. In variation 2, the average reduction in turbidity concentration was 25.08 NTU with a percentage of 70.46%, color concentration was 98.55 TCU with a percentage of 60.74%, and total coliforms were 633,000 CFU/100 mL with a percentage of 13.29%. The treatment results in this study did not meet the hygiene and sanitation water quality standards.